Sustainability-as-a-Service: Conceptualizing Value Co-Creation in Evolving Service Ecosystems - Mansouri, Youssef El Mansouri; Zahidi, Amina Zahidi; Boulif, Karim Boulif (International Journal Business and Entrepreneurship, 2025)
This conceptual paper advances the integration of sustainability and Service-Dominant Logic (S-D Logic) by proposing the notion of "Sustainability-as-a-Service." Drawing on institutional theory, complexity science, and value co-creation literature, the paper develops a multi-dimensional framework that situates sustainability as an emergent, co-created property of evolving service ecosystems. The framework comprises three interdependent dimensions: institutional orchestration, ecosystem adaptability, and sustainability value realization. These are enacted through four core capabilities—alignment, reconfiguration, capacity, and sensemaking—operating across macro, meso, and micro levels. Sustainability is thus reframed not as an outcome but as a performative process embedded in recursive service interactions and governed by dynamic institutional arrangements. Two illustrative tables explicate the constructs and levels of capability application. The discussion highlights theoretical, managerial, and policy implications, including opportunities for future empirical research. This paper contributes to midrange theory development in S-D Logic and offers a pathway for embedding sustainability within systemic design and practice. It reorients sustainability from compliance to co-creation, and from measurement to meaning.